Study of Risk Factors Associated with Neonatal Septicemia and Its Bacteriological Profile at one of the Tertiary Care Hospitals of Gujarat, India - Hardik Chauhan; Neeta Khokhar; Parul Patel; Gaurishanker Shrimali; Kiran Patel; Neha Makwana (Indian Association of Preventive and Social Medicine, 2023)
Introduction: Neonatal sepsis is a leading cause of morbidity & mortality in developing countries especially like India. As per involvement of different organisms, mortality rates differ among neonates. So, early detection of causing organism along with the identification of risk factors helps to prevent mortality among Neonates in India. Objectives: To study the risk factors associated with neonatal septicemia and its bacteriological profile at one of the tertiary care hospital of Gujarat. Method: The study was prospective observational research study in which purposive sampling technique was used to identify the 106 neonates blood culture positive to sepsis admitted in NICU of one of the tertiary care hospital in Gujarat in time period of 1 year from Nov 2021 to Oct 2022. Results: Out of 106 neonates, common factors associated with neonatal septicemia were gender, prematurity, law birth weight, gestational age & onset of septicemia. Meconium stained liquor, Pregnancy induced hypertension and Oligohydramnios were the commonest maternal risk factor associated with neonatal sepsis. Blood culture proven sepsis in neonatal septicemia was predominantly caused by Gram negative organism Klebsiella pneumonia. Conclusion: Neonatal septicemia is more common in preterm and low birth weight neonates. Early onset septicemia is more common which can be curtailed by clean vaginal deliveries. Prematurity and low birth remains the major presentation for admission in NICU followed by respiratory distress syndrome. Maternal risk factors like meconium stained liquor, pregnancy induced hypertension oligohydramnios, & leaking per -vaginal are associated With increase in the incidence of neonatal septicemia